Appearances are deceptive: a case report on subcutaneous dirofilarial granuloma mimicking a thyroglossal cyst - K. K., Adheela Nusrin; John Jacob, Amal; Kizhakkethil, Ramachandran; Narayanan, Nivee (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Dirofilarial granuloma is a nematode infestation of subcutaneous tissue transmitted by mosquito bite. This is a case of 24 year old male who presented with complaints swelling in mid region of anterior neck and on examination patient had a firm midline neck swelling 2x2cms size which had minimal movement with deglutition respiration and no movement on protrusion of tongue. Initial ultrasonogram of lesion was suggestive of a subcutaneous swelling probably thyroglossal cyst. As the clinical findings were discrepant with ultrasonogram findings we repeated imaging and repeat ultrasonogram suggested possibility of worm granuloma. Patient underwent excision and worm could be isolated from the specimen. The specimen along with worm was sent for HPE and diagnosis of dirofilarial granuloma was confirmed.